The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/s1543-5946(10)80007-8
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomy of reasons for not prescribing guideline-recommended medications for patients with heart failure

Abstract: Background Heart failure is common and highly morbid in older adults. Performance measurement systems for this condition may work best when they account for the reasons why physicians do not provide guideline-recommended interventions. Objective To develop a conceptual framework for understanding the proximate, patient-centered reasons why physicians do not prescribe ACE inhibitors and beta blockers to patients with heart failure. Design Focus group study using a two-stage design. First, we asked participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
2
26
0
1
Order By: Relevance
“…Similar to findings from a study of barriers to beta‐blocker and ACE inhibitor use in HF patients, noncardiology providers reported concerns about their respective “roles and responsibilities” (comanagement) and would defer to cardiology to initiate MRA therapy for patients who were comanaged. This reflected the sentiment that MRA therapy was a cardiology‐specific therapy outside of the norm of primary care.…”
Section: Discussionmentioning
confidence: 63%
“…Similar to findings from a study of barriers to beta‐blocker and ACE inhibitor use in HF patients, noncardiology providers reported concerns about their respective “roles and responsibilities” (comanagement) and would defer to cardiology to initiate MRA therapy for patients who were comanaged. This reflected the sentiment that MRA therapy was a cardiology‐specific therapy outside of the norm of primary care.…”
Section: Discussionmentioning
confidence: 63%
“…1, 3, 5-6, 21-23 However, it has been difficult to determine to what extent these contextual factors are truly uncommon or are simply undocumented. 19, 24-25 Our findings from clinician interviews that contextual factors were responsible for as much non-prescribing as biomedical factors suggests that performance measurement systems, most of which focus on biomedical exceptions, address only half of the issue of non-prescribing of guideline-recommended medications. This fosters a misalignment of physician incentives to provide context-sensitive care.…”
Section: Discussionmentioning
confidence: 92%
“…Reasons for not prescribing an ACE-I/ARB and/or a beta blocker were assessed based on a published taxonomy. 19 This taxonomy includes “biomedical reasons” for not receiving guideline-recommended medications for heart failure (e.g., clinical contraindications to drug therapy) and “contextual reasons,” which include the patient's life circumstances and goals as well as challenges in health care delivery (e.g., patient attitudes, competing priorities, lack of coordinated care). To be coded as a reason for non-prescribing, we required an explicit or strongly implicit statement that linked the decision not to prescribe to a specific reason for that decision (see Appendix, supplemental digital content 1 for more details).…”
Section: Methodsmentioning
confidence: 99%
“…A study about the prescription of b-blockers in patients with coronary artery disease found a similar result (35). Several patient-related reasons for potential undertreatment have been proposed (36,37), some of which are likely to differ among age groups. Aged patients have, for instance, more often comorbidities (31) and an increased risk of adverse drug events that may restrict the therapeutic options, and their treatment preferences and needs may also differ from younger patients (38).…”
Section: Discussionmentioning
confidence: 86%